2010
DOI: 10.1124/dmd.110.034918
|View full text |Cite
|
Sign up to set email alerts
|

Using Open Source Computational Tools for Predicting Human Metabolic Stability and Additional Absorption, Distribution, Metabolism, Excretion, and Toxicity Properties

Abstract: ABSTRACT:Ligand-based computational models could be more readily shared between researchers and organizations if they were generated with open source molecular descriptors [e.g., chemistry development kit (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 57 publications
(56 reference statements)
2
80
0
Order By: Relevance
“…One of the issues with computational models is that they are rarely accessible to others due to the commercial software licensing requirements. We have previously showed that models built with open source tools can produce validation statistics comparable to commercial modeling tools 49 . We recently made “function class fingerprints of maximum diameter 6” (FCFP6) and “extended connectivity (ECFP6) fingerprints,” open source and have described their implementation with the Chemistry Development Kit (CDK) 50 components 41 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the issues with computational models is that they are rarely accessible to others due to the commercial software licensing requirements. We have previously showed that models built with open source tools can produce validation statistics comparable to commercial modeling tools 49 . We recently made “function class fingerprints of maximum diameter 6” (FCFP6) and “extended connectivity (ECFP6) fingerprints,” open source and have described their implementation with the Chemistry Development Kit (CDK) 50 components 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The ADME-Tox properties may also be obtained using in silico techniques and there are several ADME-Tox methods that had been proposed [2][3][4][5]. This ADME-Tox profile is usually computed for drug candidates in the very early stage of their design [6] but it may be also substracted for other chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In some ways, there are analogous difficulties in the exchange of computational models like quantitative structure activity relationship (QSAR) datasets-while there are efforts to standardize how the data and models are stored, queried, and exchanged, there has been little consideration of licenses required to enable making the sharing of open source models a reality (Spjuth 2010;Gupta 2010). Similarly, one could consider the creation of maps of disease and how they are shared and reused [24] in the same manner (Derry et al 2012).…”
Section: Introductionmentioning
confidence: 99%